“These Groups of Islands are Different”: Identity and Constitutional Change in Orkney and Shetland, 1966-1990 - Mathew Nicolson (Revue LISA)
Between 1966 and 1990, Orkney and Shetland experienced multiple debates concerning their form of government and participation within British and Scottish constitutional structures. Chief among these were their status in Scotland’s local government system, their inclusion within schemes for Scottish devolution and the subsequent emergence of organisations campaigning for greater autonomy. The discovery of North Sea oil and resultant transformation of the islands’ social and economic fabric added fuel to these debates, contributing to the development of strengthened Shetland and Orcadian political identities. Orkney and Shetland are often portrayed as retaining a strong Norse identification at the expense of a Scottish identity. Similarly, the actions of the islands’ political leaders in this period have been characterised as the product of “anti-Scottish” sentiment. While such outlooks existed, this article adopts a more nuanced examination which accounts for Orkney and Shetland’s multi-layered identities. Rather than simply a rejection of Scottish identity and associations, these political developments should also be understood as responses to a widespread sense of vulnerability amid perceived threats towards the islands’ own local identities in a period of rapid economic, social and political change.